Subjective dimension in the analysis of human development - Domínguez-Martín, Rafael; López-Noval, Borja (Iberoamerican Journal of Development Studies, 2012)
In recent years subjective evaluations about own quality of life, resumed in levels of life satisfaction or happiness, are gaining importance as indicators of development. Some authors state that subjective well-being is a necessary and sufficient condition for human development. In this work the arguments ofthese authors are explained and it is discussed the role subjective evaluations must play on development studies. The main conclusion is that although it is necessary to integrate subjective well-being into humandevelopment studies we cannot identify subjective well-being and development.CITE AS:Domínguez-Martín, R., López-Noval, B. (2012). La dimensión subjetiva en el estudio del desarrollo humano. Iberoamerican Journal of Development Studies, 1 (1): 102-112
Keywords: happiness; subjective wellbeing; human development